2022
DOI: 10.1182/bloodadvances.2022008150
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy comparison of tisagenlecleucel vs usual care in patients with relapsed or refractory follicular lymphoma

Abstract: The ELARA trial indicates tisagenlecleucel (tisa-cel) is an effective anti-CD19 chimeric antigen receptor (CAR) T-cell therapy for relapsed/refractory follicular lymphoma (r/r FL). As ELARA is single-arm, this study compared tisa-cel outcomes from ELARA with usual care from a real-world cohort. ELARA enrolled 98 patients as of 29Mar2021 (median follow-up: 15 months from enrollment). Usual care data came from ReCORD-FL, a global retrospective study of r/r FL patients who met similar eligibility criteria to ELAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…These updated data are bolstered by recent findings from retrospective analyses (before mosunetuzumab) comparing ELARA with real-world evidence, demonstrating improved efficacy of tisagenlecleucel over other SOC options. 11 , 12 Patients from ELARA had an estimated 1.4-fold higher PFS rate at 12 months and an 80% reduction in risk of death compared with SOC. 11 Similarly, comparison of ELARA vs the US Flatiron Health Research Database indicated improved efficacy across CRR (69% vs 18%), 12-month PFS (73% vs 42%), OS (97% vs 85%), and TTNT (86% vs 52%) for tisagenlecleucel compared with SOC.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These updated data are bolstered by recent findings from retrospective analyses (before mosunetuzumab) comparing ELARA with real-world evidence, demonstrating improved efficacy of tisagenlecleucel over other SOC options. 11 , 12 Patients from ELARA had an estimated 1.4-fold higher PFS rate at 12 months and an 80% reduction in risk of death compared with SOC. 11 Similarly, comparison of ELARA vs the US Flatiron Health Research Database indicated improved efficacy across CRR (69% vs 18%), 12-month PFS (73% vs 42%), OS (97% vs 85%), and TTNT (86% vs 52%) for tisagenlecleucel compared with SOC.…”
Section: Discussionmentioning
confidence: 98%
“… 11 , 12 Patients from ELARA had an estimated 1.4-fold higher PFS rate at 12 months and an 80% reduction in risk of death compared with SOC. 11 Similarly, comparison of ELARA vs the US Flatiron Health Research Database indicated improved efficacy across CRR (69% vs 18%), 12-month PFS (73% vs 42%), OS (97% vs 85%), and TTNT (86% vs 52%) for tisagenlecleucel compared with SOC. 12 These benefits over SOC were observed regardless of number of previous therapies, requirement for bridging therapy, or POD24 status.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Toxicities were seemingly lower than those of axi-cel, with no CRS exceeding grade 2 and grade ≥ 3 ICANS of 3% [ 31 ]. Again, a propensity score matching study confirmed the stronger efficacy of CAR-T cell therapy compared to usual care both in terms of PFS and OS [ 32 ].…”
Section: Upcoming Settingsmentioning
confidence: 97%
“…In Anbetracht der Erkrankungskinetik von FL sind die Nachbeobachtungszeiten der Studien immer noch relativ kurz, zeigen jedoch langanhaltende Remissionen bei einem Teil der Patient*innen (mediane Remissionsdauer für Axi-cel 38,6 Monate, für Tisa-cel nicht erreicht [13,14]). Retrospektive Propensity-Score-gematchte Vergleiche mit historischen Kohorten deuten zudem auf eine bessere Wirksamkeit der CAR-T-Zell-Therapie im Vergleich zum bisherigen Therapiestandard hin [15,16] Merke Bispecifics stellen damit eine aussichtsreiche Therapiestrategie nach Versagen einer CD19-CAR-T-Zell-Therapie dar [20,21].…”
Section: Merkeunclassified